Stakeholders’ Perceptions of Seismic Risk and Adaptive Capacity to Earthquake: The Case of Anse-à-Veau (Haiti) - Garry Jourdan; Michelet Clerveau; Wisly Dieujuste; Sabine Henry (European Scientific Journal, ESJ, 2024)
Earthquakes were responsible for more than half of all natural disaster deaths worldwide between 2000 and 2019. Populations in developing countries are the most affected. What can help stakeholders to increase people adaptive capacity to earthquake in a context of very limited financial resources? The perception of seismic risk by the stakeholders and the perception of their adaptive capacity seemed to be able to influence the stakeholder’s adaptive capacity to earthquakes as well as that of the population. Haiti, a country at risk of earthquakes and ranked among the poorest in the world, is a relevant place to explore the potential people adaptive capacity to earthquake. In 2020, qualitative methods through face-to-face interviews were conducted with 21 stakeholders in the town of Anse-à-Veau. This paper, therefore, focuses on exploring their perceptions of risk and adaptive capacity, just one year before an earthquake in the region. The results show that stakeholders were mostly aware of earthquake risk. This was identified by their perception of seismic risk related to the zone and the perception of their adaptative capacity to deal with earthquakes. Respondents perceived that some drivers such as self-capacity, motivation, and selfresponsibility can increase their adaptive capacity. Some temporal and physical factors have been highlighted as constraints to stakeholders’ adaptive capacity to earthquake. As expected, training, awareness, and appropriate constructions were identified as effective ways to increase the adaptive capacity of stakeholders and that of the local populations to earthquakes. Currently, earthquake unpredictability was seen as a barrier of preparedness. However, some respondents perceived unpredictability as a factor of motivation for earthquake preparedness. Thus, this observation must be examined to find the way that unpredictability can facilitate stakeholders’ adaptive capacity to earthquake or not. Human resources are targeted as the main resource to cope with an earthquake. Also, training and awareness were recognized as means to increase the adaptive capacity of stakeholders and that of the local populations to deal with such an event, despite the limited financial resources.